Effects of progressive gaming sessions on cognitive awareness among Saudi education university students - Sarah M. Alajlan; Wissal Boughattas; Obaidalah H. Aljohani; Hela Znazen (Scientific Reports)
Abstract This study investigated the effects of progressive gaming sessions on metacognitive skills among 66 female’s students in KSA university. Using a standardized Tetris gaming intervention with increasing durations (20, 30, and 40 min), we measured changes in academic performance and metacognitive abilities by standardized tests and the Arabic State Metacognitive Inventory. Results showed academic performance significantly improved during 20-min sessions compared to baseline but declined during longer 30 and 40-min sessions (F = 7.82, p < 0.001). Metacognitive variables remained stable across sessions (F = 1.54, p = 0.205), with only self-checking showing significant changes. Regression analysis confirmed gaming duration negatively predicted exam performance (β = − 0.260, p < 0.001) but had no significant relationship with metacognitive variables. These findings suggest that gaming interventions require careful duration management, with shorter sessions (approximately 20 min) appearing more beneficial for academic performance while longer sessions may have diminishing returns. The stability of metacognitive variables despite fluctuations in academic performance suggests that these cognitive domains may respond differently to gaming interventions among female university students.